A clean and efficient down processing technology based on two physical methods. (August 2020) - Qiang, Taotao; Pu, Yadong; Zhang, Qi
In this study, a clean and efficient down processing technology improved the bulkiness of the down fibers by two physical methods. On the one hand, amino polysiloxane compound SI-G was used to modify down fibers physically. On the other hand, the structure of down fibers keratin was changed and the elasticity of down was increased by adjusting the temperature, so the bulkiness of down fibers was improved. The results showed that the most suitable condition for down fibers in the air-blast dusting machine was a temperature of 60 ± 2°C when the SI-G dosage was 2% of the weight of down, the performance of down fibers was the best. The bulkiness increased by 49%, the cleanliness increased by 92%, and the residual fat rate did not change significantly. Evidence was provided by scanning electron microscope and energy dispersive spectrometer (SEM-EDS), nuclear magnetic resonance spectrometer ( 13 C-NMR), X-ray Diffractometer (XRD) and Raman spectroscopy analysis. The results showed that, on the one hand, amino polysiloxane SI-G adsorbed on the down surface, making the fiber smooth, soft, and elastic. On the other hand, the conformation of down fibers keratin changed, the conformation of keratin macromolecule α-helix increased relatively, and the random crimp conformation decreased relatively, which makes the protein structure more regular and elastic, so the bulkiness of the down fibers improved.